The Development of Romantic Partner Involvement and Tolerance of Deviance among Juvenile Offenders: Relevance for Offending Behaviors in Early Adulthood. Issue 8 (2nd August 2020) - Wojciechowski, Thomas W.
ABSTRACT: This study sought to elucidate heterogeneity in developmental patterns of romantic relationship characteristics and examine the relevance of patterns for predicting offending in adulthood. Group-based trajectory modeling was used to elucidate trajectory groups describing developmental heterogeneity of odds of having a romantic partner and romantic partners' tolerance of deviance. Poisson regression was used to estimate the effects of group assignments for predicting offending. Three- and four-group models best fit the romantic partner characteristics data. Consistently high odds of having a romantic partner and consistently seeking partners with high tolerance for deviance was associated with greater offending frequency in adulthood.